2023
DOI: 10.1039/d2lc00864e
|View full text |Cite
|
Sign up to set email alerts
|

A photonic biosensor-integrated tissue chip platform for real-time sensing of lung epithelial inflammatory markers

Abstract: Tissue chip (TC) devices seek to mimic human physiology on a small scale. They are intended to improve upon animal models in terms of reproducibility and human relevance, at a...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…212 More recently, the group of Cognetti et al demonstrated the use of integrated microring resonators on so-called "disposable chips" embedding microfluidics for the detection of COVID-19 213 and real-time sensing of lung epithelial inflammatory markers (Figure 17). 214 In these original works, the researchers show the possibility to achieve organs-on-a-chip by measuring several targets secreted from cells maintained by a barrier. This innovative concept opens the way to new types of applications and real-time multiplexing.…”
Section: ■ Toward Practical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…212 More recently, the group of Cognetti et al demonstrated the use of integrated microring resonators on so-called "disposable chips" embedding microfluidics for the detection of COVID-19 213 and real-time sensing of lung epithelial inflammatory markers (Figure 17). 214 In these original works, the researchers show the possibility to achieve organs-on-a-chip by measuring several targets secreted from cells maintained by a barrier. This innovative concept opens the way to new types of applications and real-time multiplexing.…”
Section: ■ Toward Practical Applicationsmentioning
confidence: 99%
“…(f) Antibody layout showing the different target molecules for each ring resonator. Reproduced with permission from Cognetti et al Copyright 2023 The Royal Society of Chemistry.…”
Section: Toward Practical Applicationsmentioning
confidence: 99%
“…In another study, Cognetti et al developed a photonic biosensor-based monitoring system for inflammatory cytokines in a lung-on-a-chip system [42]. The biosensor consisted of two sets of 14 silicon nitride photonic ring resonators, with each set featuring an edge-coupled 8-waveguide array.…”
Section: Optical Biosensingmentioning
confidence: 99%
“…Therefore, many researchers are interested in studying defective digestive, immune, and endocrine functions as well as diseases such as infection, inflammation, and cancer using animal models. These models have been enormously challenged by unethical and costly issues caused by using different kinds of animals [ 27 , 28 , 29 , 30 , 31 ]. Therefore, a lab-on-a-chip was proposed as a solution to replace animal models with many unsolvable problems.…”
Section: Introductionmentioning
confidence: 99%